Herding behavior and the information effect of firm’s ownership - Mohd Nasarudin, Ahmad Fawwaz; Hanijito, D. Agus; Amin Noordin, Bany Ariffin; Matemilola, Bolaji Tunde (The Publisher, 2017)
Available empirical evidences reveal that macroeconomic information influences investor’s herding decision, but very limited studies focus on the influence of firm’s ownership types on investor’s herding decision. This study challenges the importance of information dissemination at firm’s level on investor’s herding decision. By categorizing firms according to family and non-family ownership, this study investigates the existence of herding in 22 different countries. Applying the cross sectional absolute deviation (CSAD), we find existence of herding activity only in Greece, New Zealand and China. Our findings suggest that investors place less importance on firm’s information dissemination management.